Distant learning organized by the Center of Excellence of Healthcare and Pharmacy Specialist - Center of Excellence of Healthcare; Pharmacy Specialists informs (Slauga. Mokslas ir praktika, 2020)
Kviečiame tobulinti savo profesinę kvalifikaciją nuotoliniu būdu.